UPAYA GURU BIMBINGAN DAN KONSELING TERHADAP KASUS PUTUS SEKOLAH SELAMA PANDEMI COVID 19 DI SEKOLAH MENENGAH KEJURUAN PROVINSI KEPULAUAN BANGKA BELITUNG - Nurviyanti Cholid; Al Fakhri Zakirman; Muhammad Sholeh Marsudi; Wilda Afiya (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
This paper aims to discuss the Guidance and Counseling Teacher Efforts Against Dropout Cases During the Covid 19 Pandemic at Vocational High Schools in the Bangka Belitung Islands Province, which includes the efforts that have been made by BK teachers in preventing dropout cases during the covid pandemic and the factors that affect children dropping out of school during the covid 19 pandemic. The method used is descriptive qualitative and analyzed with an interactive analysis model by collecting data, reducing data and concluding data. The results of the discussion show that the factors that cause school dropouts during the Covid-19 Pandemic in Vocational High Schools in the Bangka Belitung Islands Province consist of: First, internal factors originating from within the students themselves, namely the lack of motivation to learn in students, and students having difficulty learning online at the time of the Covid-19 pandemic. Second, external factors that come from outside which include the lack of parental support in learning, students working with parents in the plantation and IT sectors, external environmental influences such as online games, and juvenile delinquency, as well as cases of pregnancy outside marriage. and Counseling for dropout cases during the Covid-19 pandemic at Vocational High Schools in the Bangka Belitung Islands Province are through: First, Preventive Efforts, namely by conducting Placement and Distribution Services, Orientation Services, Classical Guidance Services and school involvement. Second, curative efforts, namely by carrying out Home Visit Support Services, Individual Counseling, and Stop Outs.